Influence of artificial drainage system design on the nitrogen attenuation potential of gley soils: Evidence from hydrochemical and isotope studies under field-scale conditions - Clagnan, E.; Thornton, S.F.; Rolfe, S.A.; Tuohy, P.; Peyton, D.; Wells, Naomi Susan; Fenton, O. (Journal of Environmental Management, 2017)
In North Atlantic Europe intensive dairy farms have a low nitrogen (N) use efficiency, with high N surpluses often negatively affecting water quality. Low feed input systems on heavy textured soils often need artificial drainage to utilise low cost grassland and remain profitable. Heavy textured soils have high but variable N attenuation potential, due to soil heterogeneity. Furthermore, drainage system design can influence the potential for N attenuation and subsequent N loadings in waters receiving drainage from such soils. The present study utilises end of pipe, open ditch and shallow groundwater sampling points across five sites in SW Ireland to compare and rank sites based on N surplus, water quality and “net denitrification”, and to develop a conceptual framework for the improved management of heavy textured dairy sites to inform water quality N sustainability. This includes both drainage design and “net denitrification” criterion, as developed within this study.N surplus ranged from 211 to 292 kg N/ha (mean of 252 kg N/sourha) with a common source of organic N across all locations. The predicted soil organic matter (SOM) N release potential from top-subsoil layers was high, ranging from 115 to >146 kg N/ha. Stable isotopes analyses showed spatial variation in the extent of specific N-biotransformation processes, according to drainage location and design. Across all sites, nitrate (NO3-N) was converted to ammonium (NH4+-N), which migrated offsite through open ditch and shallow groundwater pathways. Using the ensemble data the potential for soil N attenuation could be discriminated by 3 distinct groups reflecting the relative dominance of in situ N-biotransformation processes deduced from water composition: Group 1 (2 farms, ranked with high sustainability, NH4+ < 0.23 mg N/l, δ15N-NO3− > 5‰ and δ18O-NO3− > 10‰), low NH4+-N concentration coupled with a high denitrification potential; Group 2 (1 farm with moderate sustainability, NH4+ < 0.23 mg N/l, δ15N-NO3− < 8‰ and δ18O-NO3− < 8‰), ...